An entry game with learning and market competition - Chia-Hui Chen; Junichiro Ishida; Arijit Mukherjee (Osaka University, Institute of Social and Economic Research (ISER), 2018)
This paper provides a dynamic game of market entry to illustrate entry dynamics in an uncertain market environment. Our model features both private learning about the market condition and market competition, which give rise to the first-mover and secondmover advantages in a unified framework. We characterize symmetric Markov perfect equilibria and identify a necessary and sufficient condition for the first-mover advantage to dominate, which elucidates when and under what conditions a firm becomes a pioneer, an early follower or a late entrant. We also derive equilibrium payoff bounds to show that pioneering entry is generally payoff-enhancing, even though it is driven by preemption motives, and discuss efficiency properties of entry dynamics.
Keywords: D82; D83; L13; 330; market entry; market competition; private learning; signaling; entry timing